2021
DOI: 10.3390/agriculture11050407
|View full text |Cite
|
Sign up to set email alerts
|

Sugar Beet Root Yield and Quality with Leaf Seasonal Dynamics in Relation to Planting Densities and Nitrogen Fertilization

Abstract: This study aimed to analyze the seasonal dynamics of sugar beet leaf and root yield and quality in different plant populations and the nitrogen fertilization rate. The field trials were set as four different planting densities (60,000 to 140,000 plants ha−1) and three different spring nitrogen fertilization rates: no fertilization, pre-sowing (45 kg ha−1 N), and pre-sowing with top dressing (99 kg ha−1 N in 2014 and 85.5 kg ha−1 N in 2015. The changes of leaf growth were done measuring leaf area (LA), leaf are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…These results were consistent with those of Sogut and Arioğlu (2004). Varga et al, (2020) and Varga et al, (2021) also proposed similar experimental results. Sugar beet with densities of 100000 plants/ha and 140000 plants/ha, or no less than 100000 plants/ha, both had higher yield and quality.…”
Section: Discussionsupporting
confidence: 91%
“…These results were consistent with those of Sogut and Arioğlu (2004). Varga et al, (2020) and Varga et al, (2021) also proposed similar experimental results. Sugar beet with densities of 100000 plants/ha and 140000 plants/ha, or no less than 100000 plants/ha, both had higher yield and quality.…”
Section: Discussionsupporting
confidence: 91%
“…The obtained increase in sugar yield by adding 120 kg N/fed (Table 4) may be referred to as the increase in root yield/fed (Table 3), which compensated for the decrease in sucrose percentage. In line with these results, Varga et al 29 proved that application of 99 kg N/ha produced maximum root and sugar yields haG 1 , versus a reduction in sucrose content. This trend supports the collected results in Table 3 and 4.…”
Section: Discussionmentioning
confidence: 70%
“…Also, the distinct effect of 20 and 25 cm distances on LAI is mainly due to the favorable climatic conditions especially the light intensity which accelerated vegetative growth, formation of good canopy capable to increase LAI. Conversely, Varga et al (2021) found that the highest LAI was obtained with the higher plant densities i.e. 140000 and 100000 plants/ha than 60000 plants/ha.…”
Section: Resultsmentioning
confidence: 83%
“…However, an insignificant difference among sowing hills i.e.15, 20 and 25 cm were found in their influence on impurities content, purity% and sucrose%. Varga et al (2021) found that the highest values of LAI, root and white sugar yields/ha were obtained when the beet plant densities were 140000 and 100000 plants/ha, in the 1 st and 2 nd season, respectively, than 60000 plants/ha.…”
Section: Introductionmentioning
confidence: 91%